EFFECT OF MULTI - ENZYME ON PRODUCTION PERFORMANCE AND CARCASS TRAITS OF NANDANAM BROILER - 2 CHICKENS - K. Sangilimadan; A.V.Omprakash; K.Premavalli; C.Pandian; R.Richard Churchill (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted at Institute of Poultry Production and Management (IPPM), Madhavaram Milk colony, Chennai-51.Three hundred and sixty (360) day-old straight run Nandanam broiler - 2 chicks were individually weighed, wing banded and randomly assigned to three different dietary treatments with two replicates and reared on deep litter system for a period of 8 weeks. The results showed that supplementation of muti-enzyme at the rate of 500g per ton of feed (T2) in Nandanam broiler-2 ration were significantly higher (P<0.01) than control in weight gain of 2nd, 8th and 0-8 week of age. The feed consumption and feed conversion efficiency was significantly higher (P<0.01) in control compared to treatment. The livability was highly significant (P<0.01) in T3 than control. The carcass characteristics of live weight, heart, eviscerated, giblet and ready-to-cook weight did not show any significant difference in treatment group than control. The cut-up parts of breast yield were highly significant (P<0.01) in T2 than control. The drumstick yield was significantly higher (P<0.01) in control than treatments. The cut-up-parts of back, thigh, neck and wing did not show any significant difference in treatment than the control, but the value was better in enzyme treated group. It was concluded that the production performance was better in supplementation of multi – enzyme at the rate of 500g/ ton of feed and carcass traits was not significantly different between the treatments.